1995
DOI: 10.1080/0141192950210105
|View full text |Cite
|
Sign up to set email alerts
|

Birth Date and Sex Effects on the Scholastic Attainment of Primary Schoolchildren: a cross‐sectional study

Abstract: The aim of this study was to investigate the role of pupil age as a major cause of the birth date effect in scholastic performance. Sex differences in performance were also investigated. A sample of 4123 pupils in Grades III, IV and V was selected from 12 state primary schools in Malta. Since in this educational setting there is only one intake of pupils per scholastic year it ensured that all children within any given year group would have received the same length of formal schooling. Analyses based on a data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
3
13
1
Order By: Relevance
“…Thirdly, in the present study, the differences in achievement between the younger and older school entrants were observed across different subjects, to examine their consistency. In some studies, older students outperform the younger ones across subjects (e.g., Borg & Falzon, ; Kalk et al ., ; Sharp et al ., ; Teltsch & Breznitz, ). On the other hand, Cobley et al .…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, in the present study, the differences in achievement between the younger and older school entrants were observed across different subjects, to examine their consistency. In some studies, older students outperform the younger ones across subjects (e.g., Borg & Falzon, ; Kalk et al ., ; Sharp et al ., ; Teltsch & Breznitz, ). On the other hand, Cobley et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that relatively older students in the same cohort achieve more in school (Thompson (1971), Allen and Barnsley (1993), Borg and Falzon (1995), and Lien et al (2005)), are less likely to be diagnosed as having specific learning disabilities (Martin et al (2004)), are less likely to commit suicide (Thompson et al (1999)), and are more likely to be class leaders in high school (Dhuey and Lipscomb (2008)). Relative age effects also are found in the field of sports (Dudink (1994) and Helsen et al (2000)).…”
Section: Introductionmentioning
confidence: 99%
“…This could be partially explained by the existence of studies proving that girls consistently outperform boys in scholastic attainment in primary and secondary studies [6], meaning that in the end a disproportionately greater proportion of women gains admittance to university. In addition, a study of the birth dates, sex and cognitive abilities of children with special educational needs showed that males were significantly over-represented compared to females [20].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases the asymmetric age distribution could be explained by the specific abilities in mathematics required in these studies. Analyses based on a data set consisting of mathematics scores showed a strong and consistent age effect: the 'oldest' pupils in an age class were better in mathematics than the 'youngest' pupils [6,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation